Scaling the impact of the energy transition through inclusivity and diversity across living labs - Julia Epp; Muhittin Hakan Demir; Lucia Liste; Berit T. Nilsen; Marlyne Sahakian; Mallory Zhan; Christiane Walter; Mehmet Efe Biresselioglu (Sustainability: Science, Practice, & Policy)
The energy transition has not benefited all segments of society equally, raising critical questions about the design of just energy policies and projects. This inequity highlights the need for inclusive approaches, especially within living labs piloting sustainable energy solutions. A key challenge for living labs is achieving broad societal impact, which is fundamentally tied to inclusivity. Living lab research must prioritize diversifying participants and stakeholders to effectively scale solutions across diverse communities. Individual characteristics, such as gender, ethnic identity, level of education, wealth, and income, strongly influence the ability to participate in energy projects. As spaces for co-production and transformation, living labs should fully embrace diversity as a key principle, fostering deliberative exchange connecting actors from different backgrounds. The European Green Deal prioritizes a “just transition,” signaling the political demand to develop transdisciplinary research projects that address issues such as energy poverty, the gender pay gap, and social segregation. To investigate this disparity, we designed and implemented four citizen action labs in Germany, Norway, Switzerland, and Türkiye, experimenting with different notions of inclusivity and diversity. Based on our findings, we explore the concept of inclusivity at the sociopolitical context (scaling up), stakeholder, and population locality (scaling deep and scaling out). In particular, we focus on the role of recruitment as a bottleneck for diverse public engagement. Leveraging the knowledge gained from the research process, this article provides evidence for setting up living labs in the energy transition, targeting distinctive social groups to create a meaningful impact across society.